(untitled) (Al-Academy, 2018)
The present research is concerned with the way in which different dialects interact with each other in contemporary sculpture through the use of the metaphor for various shapes, meanings and materials and placing them in contexts that conflict with the familiar. These attempts come in harmony with the spirit of the times in seeking exoticism, surprise and splendor as a means of renewal. modern Art . Therefore, the research was divided into four axes, the first of which included the research problem, its importance and its aim, which is to attempt to uncover the metaphorical metaphorical relational mechanism in modern sculpture. The second axis included the theoretical framework. The third axis included the research procedures of determining the society and how to select the sample, And the fourth and final axis to review the results reached by the research was that the mechanism of metaphor in contemporary sculpture is not an aesthetic technique, but the availability of a basic pillar in the framework of semantic connection, that is in the relationship form and meaning other forms and meanings of neighboring may be from The same sex or that of another race, which leads to the creation of a new work of art overlaps with many technical texts